2003
DOI: 10.1136/jech.57.5.385
|View full text |Cite
|
Sign up to set email alerts
|

Relation between number of siblings and adult mortality and stroke risk: 25 year follow up of men in the Collaborative study

Abstract: Study objective: To investigate the relation between number of siblings, mortality risk, and stroke risk. Design: Prospective cohort study. Setting: 27 workplaces in Scotland. Participants: 5765 employed men aged 35-64 from a variety of different workplaces, screened between 1970 and 1973. Main results: There were strong relationships between number of siblings and socioeconomic variables and also with adult behavioural measures. Men with greater numbers of siblings had an increased risk of dying of all causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
79
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 37 publications
4
79
1
Order By: Relevance
“…Furthermore, this weak increase in risk was not confirmed for CHD or stroke mortality. Hart et al reported a higher risk of haemorrhagic stroke with greater number of siblings [7] but in the current study there were insufficient confirmed deaths from haemorrhagic and ischemic stroke to assess these outcomes separately. We did not find a previously reported higher mortality due to stomach cancer [7], which is thought to indicate a higher risk of infection by Helicobacter Pylori in childhood.…”
Section: Introductionmentioning
confidence: 38%
See 4 more Smart Citations
“…Furthermore, this weak increase in risk was not confirmed for CHD or stroke mortality. Hart et al reported a higher risk of haemorrhagic stroke with greater number of siblings [7] but in the current study there were insufficient confirmed deaths from haemorrhagic and ischemic stroke to assess these outcomes separately. We did not find a previously reported higher mortality due to stomach cancer [7], which is thought to indicate a higher risk of infection by Helicobacter Pylori in childhood.…”
Section: Introductionmentioning
confidence: 38%
“…Hart et al reported a higher risk of haemorrhagic stroke with greater number of siblings [7] but in the current study there were insufficient confirmed deaths from haemorrhagic and ischemic stroke to assess these outcomes separately. We did not find a previously reported higher mortality due to stomach cancer [7], which is thought to indicate a higher risk of infection by Helicobacter Pylori in childhood. Increasing sibling number can lead to a higher transmission rate of an infectious agent, but this may actually occur only in the presence of other risk factors, such as overcrowding.…”
Section: Introductionmentioning
confidence: 38%
See 3 more Smart Citations